Individual and Collective Identity between 1918 and 2018 - Ionuț Mihai POPESCU (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2020)
At the beginning of the twentieth century, nationality was the most important element of collective identity, but it already heralded an era of decline of this collective identity. The assertion of the individual and of their rights as well as the disappearance of the seduction exercised by the great ideals brought two great challenges: What is the principle of solidarity (collective identity) according to which a community is organized? How can societies with a diluted collective identity meet non-conflictingly with those with a strong collective identity? The answers are still to be discovered; we only have reference points. What we can say for sure is that it is very tempting to revert to the former strong collective identity, but it only generates bigger issues than the ones it seems to solve. We consider that the care for the only available world, the reflective assumption of options of collective identity that were previously self-evident, the cultivation of “capillary” ties between individuals with different collective identities and defining a public space meant to develop the specificity of the individual, without breaking the solidarity of the community, are among the landmarks that indicate the direction of the answers to the challenges mentioned above.